Costello Syndrome and Umbilical Ligament Rhabdomyosarcoma in Two Pediatric Patients: Case Reports and Review of the Literature - Carlos Sánchez-Montenegro; Alejandra Vilanova-Sánchez; Saturnino Barrena-Delfa; Jair Tenorio; Fernando Santos-Simarro; Sixto García-Miñaur; Pablo Lapunzina; Leopoldo Martínez-Martínez (Case Reports in Genetics)
Costello syndrome is caused by heterozygous de novo missense mutations in the protooncogene HRAS with tumor predisposition, especially rhabdomyosarcoma. We here report two pediatric patients with Costello syndrome and umbilical ligament rhabdomyosarcoma. A review of the literature published in English in MEDLINE from January 1971 to June 2016 using the search terms “Costello syndrome” and “rhabdomyosarcoma” was performed, including two new cases that we describe. Twenty-six patients with Costello syndrome and rhabdomyosarcoma were recorded with mean age of diagnosis of 2 years and 8 months. The most common tumor location was the abdomen/pelvis, including four out of ten of those in the umbilical ligament. The most common histological subtype was embryonal rhabdomyosarcoma. Overall survival was 43%. A total of 17 rhabdomyosarcomas in pediatric patients arising in the umbilical ligament were recorded with mean age of diagnosis of 3 years and 4 months. Overall survival was 69%. Costello syndrome is a poorly known disorder in pediatric oncology but their predisposition to malignancies implies the need for a new perspective on early diagnosis and aggressive medical and surgical treatment.